Impurity effects in quasiparticle spectrum of high-Tc superconductors (Review Article): - Pogorelov, Yu.G.; Santos, M.C.; Loktev, V.M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
The revision is made of Green function methods that describe the dynamics of electronic quasiparticles in disordered superconducting systems with d-wave symmetry of order parameter. Various types of impurity perturbations are analyzed within the simplest T-matrix approximation. The extension of the common selfconsistent T-matrix approximation (SCTMA) to the so-called group expansions in clusters of interacting impurity centers is discussed and hence the validity criteria for SCTMA are established. A special attention is payed to the formation of impurity resonance states and localized states near the characteristic points of energy spectrum, corresponding to nodal points on the Fermi surface.